Управління оборотними активами підприємства: теоретичний аспект - Савінова, Алла В'ячеславівна (НТУ "ХПІ", 2017)
Статтю присвячено дослідженню теоретичних аспектів управління оборотними активами підприємства. Проаналізовано різні підходи вітчизняних та зарубіжних учених до визначення економічної сутності оборотних активів. Розглянута система управління оборотними активами підприємства. Систематизовано основні напрями підвищення ефективності використання оборотних засобів підприємства в сучасних умовах. В роботі висвітлено проблеми необхідності планування оборотних активів підприємств як важливої умови їх ефективного функціонування.

The article deals with the features on management of current assets at the enterprise. The main goal and tasks on management of working assets of the enterprise are determined. Theoretical aspects of management of current assets of the enterprise are researched. Different approaches of domestic and foreign scientists to the definition on the economic essence of working capital are analyzed. The system on management of current assets of the enterprise is considered. The main directions on increasing the efficiency of using circulating assets on the enterprise in the modern conditions are systematized. The problems of t he necessity on planning of current assets on enterprises as an important condition of their effective functioning are highlighted in the paper. The advantages that the company can achieve in the case of ensuring effective management of its current assets is determined.
Management of working assets of the enterprise: theoretical aspect
Keywords: методи планування; оборотні кошти; оборотний капітал; фінансові ресурси; current assets; methods of planning; management; working capital